Sustainable supply chain management: potential and challenges of implementing blockchain technology in the food supply chain of small and medium-sized companies - Harms, Julia (2020)
Sustainability in all areas of life is one of the greatest social challenges of our time. In the course of addressing these challenges, the United Nations has implemented 17 sustainable development goals. To achieve these, solutions are being pursued in the field of digitisation. Emerging technologies like, artificial intelligence, internet of things, robots and blockchain have one of the greatest potentials for changing the social and economic progress. The development towards a new kind of sustainable awareness and challenges in the food industry force companies to create and implement sustainable actions. Companies are faced with new requirements in their food supply chain in order not to lose their position in the market. As a potential solution, the link between blockchain technology and sustainability food supply chain of SME´s has been analysed. The enormous potentials are opposed by risks that have not been researched yet, especially for German SME's. Blockchain has a distributed ledger can open a significant advantage to the food supply chain, due to their trace- and track ability, but are still in an early stage of development. Their influence and significance on the food industry is constantly increasing and thus also on the supply chain management of companies. The aim of this thesis is to determine the importance of sustainable supply chain management of SME´s operating in the food sector with the help of the blockchain technology, and to evaluate the potentials and risks in the German food market.